Where sexuality and spirituality meet: An assessment of Christian teaching on sexuality and marriage in relation to the reality of 21st century moral norms - Marilize E. Tukker (HTS Teologiese Studies/Theological Studies, 2013)
Christians and the church tend to shy away from talking about sex, premarital sex and sex outside of marriage. God and sex are rarely mentioned in the same sentence, and yet people still have a deep need for spirituality, to experience God in their lives and to seek guidance on sexual matters. It becomes a dilemma when the question is posed: where do sexuality and spirituality meet? One way to answer this question is to attempt to find a link between spirituality and sexuality. In this way, spirituality could gain relevance, and expressing one’s sexuality could find a moral foundation. People are both spiritual and sexual creatures – with the need to express their spirituality and sexuality in a moral, but unashamedly natural way. This article attempts to find alternative solutions for our complex society – on the subject of marriage and sexuality. The intention is not to dismiss the institution of marriage, but rather to renegotiate the terms and structure of marriage in the 21st century.